Study protocol for a randomized double-blinded placebo-controlled trial on ASA therapy for patients with chronic rhinosinusitis with nasal polyps, NSAID-exacerbated respiratory disease, and asthma - Toppila-Salmi, Sanna; Lyly, Annina; Salmi, Viljami; Nuutinen, Mikko; Kilpiö, Michael; Hanif, Tanzeela; Niemi, Mikko; Laulajainen-Hongisto, Anu; Hafrén, Lena; Mäkelä, Mika; Kauppi, Paula; Virkkula, Paula; et al. (Frontiers in Allergy, 2025)
BackgroundChronic rhinosinusitis with nasal polyps (CRSwNP) is a chronic inflammatory condition affecting the nasal passages and paranasal sinuses. It is characterized by persistent inflammation and often leads to a considerable decline in health-related quality of life (HRQoL). A subset of these patients—approximately 17.7%—have NSAID-exacerbated respiratory disease (N-ERD), a more severe form that frequently necessitates repeated sinus surgeries and rescue therapies. Compared with individuals without N-ERD, affected patients are more prone to asthma flare-ups, severe hypersensitivity reactions, and loss of smell. Treatment with acetylsalicylic acid (ASA) following desensitization (ATAD) has been suggested as a therapeutic option in cases of severe CRSwNP with N-ERD. While this approach may offer symptom improvement, decreased polyp burden, and enhanced QoL, it is not without risks, such as gastrointestinal irritation and bleeding complications. This randomized, double-blind, placebo-controlled clinical trial (RDBCT) assesses the effectiveness and safety of ATAD in comparison with placebo in patients suffering from severe CRSwNP, N-ERD, and asthma. The study explores various outcomes, including reduction in polyp burden, improvement in QoL, treatment-related side effects, and biomarker analyses derived from nasal swabs, blood, and urine samples.MethodsAirGOs Medical is an investigator-initiated RDBCT conducted at Helsinki University Hospital. Participants are randomized to receive either ATAD or placebo. The primary endpoint is the change in the SNOT-22 score observed at the 11-month follow-up. Secondary measures include variations in nasal polyp scores, CRS symptom control, general HRQoL, work productivity loss, peak nasal inspiratory flow (PNIF) with or without acoustic rhinometry (ARM), olfactory function assessed by the Sniffin' Sticks identification test, spirometry, peak expiratory flow (PEF), and histopathological findings at the 12-month follow-up.DiscussionThe AirGOs Medical trial is expected to generate data on the therapeutic value and safety profile of ATAD in patients with coexisting severe CRSwNP, N-ERD, and asthma, potentially informing future clinical practice. Trial registration[ClinicalTrials.gov], identifier [NCT03825757]. Registered on 28.2.2019.